Biotic and Abiotic Constraints in Mungbean Production—Progress in Genetic Improvement - Nair, Ramakrishnan M.; Pandey, Abhay K.; War, Abdul R.; Hanumantharao, Bindumadhava; Shwe, Tun; Alam, AKMM; Pratap, Aditya; Malik, Shahid R.; Karimi, Rael; Mbeyagala, Emmanuel K.; Douglas, Colin A.; Rane, Jagadish; et al. (Frontiers in Plant Science, 2019)
Mungbean [Vigna radiata (L.) R. Wilczek var. radiata] is an important food and cash legume crop in Asia. Development of short duration varieties has paved the way for the expansion of mungbean into other regions such as Sub-Saharan Africa and South America. Mungbean productivity is constrained by biotic and abiotic factors. Bruchids, whitefly, thrips, stem fly, aphids and pod borers are the major insect-pests. The major diseases of mungbean are yellow mosaic (viral), anthracnose, powdery mildew, Cercospora leaf spot, dry root rot (fungal), halo blight, bacterial leaf spot and tan spot (bacterial). Key abiotic stresses affecting mungbean production are water-logging, salinity and heat stress. Mungbean breeding has been critical in developing varieties with resistance to biotic and abiotic factors, but there are many constraints still to be addressed that include the precise and accurate identification of resistance source(s) for some of the traits and the traits being conferred by multi genes. Latest technologies in phenotyping, genomics, proteomics and metabolomics could be of great help to understand insect/pathogen-plant, plant-environment interactions and the key components responsible for resistance to biotic and abiotic stresses. This review discusses current biotic and abiotic constraints in mungbean production and the challenges in genetic improvement.